Carbon-based bimetallic hydrogen storage material rich in surface defects and a method for preparing the same
Patent Information
- Application Number
- CN202410519581.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-28
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-04-28
AI Technical Summary
[0008]本发明的目的在于解决现有的固态储氢材料在室温下储氢容量低的技术问题,提出一种富含表面缺陷的碳基双金属储氢材料及其制备方法
[0021]本发明提出的富含表面缺陷的碳基双金属储氢材料的制备方法,通过在聚丙烯腈衍生多孔碳表面调控空位,增加了合金纳米颗粒的锚定点位,使得合金纳米颗粒不易发生团聚,提升了金属利用率和分散性,又通过双金属源水溶液同时逐滴加入,可以使双金属更加充分地分散在富含表面缺陷的聚丙烯腈衍生多孔碳表面的空位内,为氢气提供了更多的吸附活性位点,从而解决了室温下储氢容量低。
Smart Images

Figure CN118405657B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of solid hydrogen storage material preparation, and in particular to a carbon-based bimetallic hydrogen storage material rich in surface defects and its preparation method. Background Technology
[0002] Global environmental problems are becoming increasingly prominent, posing a dual threat of energy shortages and environmental pollution.
[0003] Hydrogen energy boasts high energy density, is renewable, provides continuous power, and produces no pollutants upon combustion, making it considered the most ideal clean energy source to replace fossil fuels. However, large-scale and safe storage of hydrogen is currently difficult, making the development of hydrogen storage technology crucial for the sustainable development of hydrogen energy.
[0004] Solid-state hydrogen storage technology has advantages such as high hydrogen storage density, small volume, high safety, and convenient transportation. However, its current application is limited by the incompatibility between the cost, storage capacity, and cycle stability of hydrogen storage materials. Therefore, researchers urgently need to further develop new solid-state hydrogen storage materials to reduce their cost and improve their storage capacity and cycle stability.
[0005] Porous carbon materials are a class of high-performance adsorbent materials with advantages such as high porosity, high specific surface area, large adsorption capacity, high surface activity, long cycle life and low cost, and are therefore widely studied in the field of hydrogen storage.
[0006] Polyacrylonitrile (PAN) is an inexpensive polymer that can be used to obtain nitrogen-doped porous carbon with a large specific surface area and pore capacity through chemical activation. Polyacrylonitrile-derived porous carbon (PANPC) stores hydrogen through physical adsorption and exhibits excellent hydrogen storage performance at low temperatures (77K), but its hydrogen storage performance is poor at room temperature.
[0007] To improve the room-temperature hydrogen storage performance of porous carbon materials, an effective strategy is to introduce metal or alloy nanoparticles onto the surface of the porous carbon material. However, metal or alloy nanoparticles have high surface energy and are prone to aggregation, resulting in poor cycling stability of the hydrogen storage material. Summary of the Invention
[0008] The purpose of this invention is to solve the technical problem of low hydrogen storage capacity of existing solid hydrogen storage materials at room temperature, and to propose a carbon-based bimetallic hydrogen storage material rich in surface defects and its preparation method.
[0009] To achieve the above objectives, the present invention adopts the following technical solution:
[0010] A method for preparing a carbon-based bimetallic hydrogen storage material rich in surface defects includes the following steps: S1: heat-treating polyacrylonitrile to obtain polyacrylonitrile pre-oxidized carbon; S2: impregnating the polyacrylonitrile pre-oxidized carbon in an activator solution and calcining it in a nitrogen atmosphere to obtain polyacrylonitrile-derived porous carbon; S3: calcining the polyacrylonitrile-derived porous carbon in a protective atmosphere to adjust the vacancies on the polyacrylonitrile-derived porous carbon to obtain polyacrylonitrile-derived porous carbon rich in surface defects; S4: dispersing the polyacrylonitrile-derived porous carbon rich in surface defects in a solution, simultaneously adding metal source solution A and metal source solution B dropwise, stirring and drying, and then calcining it in a mixed atmosphere of hydrogen and argon to obtain a carbon-based bimetallic hydrogen storage material rich in surface defects.
[0011] In some embodiments of the present invention, in step S1, the molecular weight of the polyacrylonitrile is 90,000-100,000; the temperature of the heat treatment is 240-260°C; and the heat treatment time is 2 hours.
[0012] In some embodiments of the present invention, in step S2, the calcination temperature in a nitrogen atmosphere is 700-900°C, the calcination time is 90 min, and the calcination heating rate is 1-5°C / min.
[0013] In some embodiments of the present invention, in step S2, the mass ratio of the polyacrylonitrile pre-oxidized carbon to the activator is 1:1 to 1:15, and the activator includes at least one of potassium hydroxide, potassium chloride, and potassium carbonate.
[0014] In some embodiments of the present invention, step S2, when immersing the polyacrylonitrile pre-oxidized carbon in a solution of an activator, further includes stirring and drying, followed by calcination in a nitrogen atmosphere, and then cooling, cleaning, and drying; the activator contains potassium hydroxide, and before cleaning, hydrochloric acid aqueous solution is used to neutralize the remaining potassium hydroxide to remove potassium hydroxide from the polyacrylonitrile-derived porous carbon.
[0015] In some embodiments of the present invention, in step S3, the protective atmosphere is air, the calcination temperature is 350-450°C, the calcination time is 10-20 min, the calcination heating rate is 1-5°C / min, and the vacancy is a carbon vacancy, thereby obtaining polyacrylonitrile-derived porous carbon with carbon vacancy.
[0016] In some embodiments of the present invention, in step S3, the protective atmosphere is a mixture of hydrogen and argon, the calcination temperature is 400-850°C, the calcination time is 10-20 min, the calcination heating rate is 1-5°C / min, and the vacancy is an oxygen vacancy, thereby obtaining polyacrylonitrile-derived porous carbon with oxygen vacancies.
[0017] In some embodiments of the present invention, in step S4, metal A is one of palladium, gold, silver, iron, cobalt, nickel, and copper, and metal B is one of palladium, gold, silver, iron, cobalt, nickel, and copper; metal A and metal B are not the same; metal A and metal B are derived from water-soluble metal salts of the corresponding metals, the concentration of metal A is 1-10 wt.%, and the concentration of metal B is 0-5 wt.%.
[0018] In some embodiments of the present invention, in step S4, the solution is deionized water and is ultrasonically vibrated for 15 min; simultaneously, when adding the A metal source solution and the B metal source solution, the dropping rate is 1 drop / 10 s, so that the A metal and the B metal are well dispersed on the surface of the polyacrylonitrile-derived porous carbon rich in surface defects; when calcining in a mixed atmosphere of hydrogen and argon, the calcination temperature is 400-900℃, the calcination time is 120 min, and the calcination heating rate is 3-5℃ / min.
[0019] The present invention also proposes a carbon-based bimetallic hydrogen storage material rich in surface defects, which is obtained by the preparation method of carbon-based bimetallic hydrogen storage material rich in surface defects as described in any one of the above.
[0020] The present invention has the following beneficial effects:
[0021] The method for preparing carbon-based bimetallic hydrogen storage materials rich in surface defects proposed in this invention increases the anchoring sites of alloy nanoparticles by controlling vacancies on the surface of polyacrylonitrile-derived porous carbon, making the alloy nanoparticles less prone to aggregation and improving metal utilization and dispersibility. Furthermore, by simultaneously adding bimetallic source aqueous solution dropwise, the bimetal can be more fully dispersed in the vacancies on the surface of polyacrylonitrile-derived porous carbon rich in surface defects, providing more adsorption active sites for hydrogen, thereby solving the problem of low hydrogen storage capacity at room temperature.
[0022] The carbon-based bimetallic hydrogen storage material rich in surface defects was tested for hydrogen storage performance and showed that it has high hydrogen storage capacity and good cycle stability, and has broad application prospects in the field of hydrogen storage.
[0023] Other beneficial effects of the embodiments of the present invention will be further described below. Attached Figure Description
[0024] Figure 1 The image shows a scanning electron microscope (SEM) image of the PANPC synthesized in Example 1.
[0025] Figure 2 The image shows a transmission electron microscope (SEM) image of the PANPC-OSD synthesized in Example 1.
[0026] Figure 3 The image shows a scanning electron microscope (SEM) image of the Pd3Ni1 / PANPC-OSD synthesized in Example 1.
[0027] Figure 4 The image shows a transmission electron microscope (TEM) image of the Pd3Ni1 / PANPC-OSD synthesized in Example 1.
[0028] Figure 5 Here is a scanning electron microscope (SEM) image of the PANPC-CSD synthesized in Example 2;
[0029] Figure 6 The image shows a scanning electron microscope (SEM) image of the Pd3 / PANPC-OSD synthesized in Comparative Example 1.
[0030] Figure 7 The image shows a scanning electron microscope (SEM) image of the Ni1 / PANPC-OSD synthesized in Comparative Example 2.
[0031] Figure 8 The image shows a scanning electron microscope (SEM) image of Ag4Ni1 / PANPC synthesized in Comparative Example 3.
[0032] Figure 9A PCT curves of hydrogen storage materials of Example 1, Comparative Example 1 and Comparative Example 2 at 77K;
[0033] Figure 9B PCT curves of the hydrogen storage materials synthesized in Example 1, Comparative Example 1, and Comparative Example 2 at 298 K;
[0034] Figure 10A The curves showing the change in hydrogen storage capacity over time for the hydrogen storage materials of Example 1, Comparative Example 1, and Comparative Example 2 at 77K are shown.
[0035] Figure 10B The curves showing the change in hydrogen storage capacity over time for the hydrogen storage materials of Example 1, Comparative Example 1, and Comparative Example 2 at 298K are shown.
[0036] Figure 11 Example 1 shows the hydrogen storage capacity retention rate of the hydrogen storage material under 77K conditions during cycling.
[0037] Figure 12A PCT curves of the hydrogen storage materials of Example 2 and Comparative Example 3 at 77 K;
[0038] Figure 12B PCT curves of the hydrogen storage materials of Example 2 and Comparative Example 3 at 298 K;
[0039] Figure 13A The hydrogen storage capacity of the hydrogen storage materials in Example 2 and Comparative Example 3 changes over time at 77K.
[0040] Figure 13B The hydrogen storage capacity of the hydrogen storage materials in Example 2 and Comparative Example 3 changes over time at 298K.
[0041] Figure 14 Example 2 shows the hydrogen storage capacity retention rate of the hydrogen storage material under 77K conditions during cycling.
[0042] Figure 15 This is a flowchart illustrating the steps of a method for preparing a carbon-based bimetallic hydrogen storage material rich in surface defects according to an embodiment of the present invention. Detailed Implementation
[0043] The present invention will be further described below with reference to the accompanying drawings and preferred embodiments. It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other.
[0044] It should be noted that the directional terms such as left, right, up, down, top, and bottom in this embodiment are only relative concepts or are based on the normal use of the product, and should not be considered as restrictive.
[0045] PANPC possesses a large specific surface area, providing active sites for the growth of bimetallic nanoparticles. Numerous studies have demonstrated a positive correlation between the hydrogen storage capacity of porous carbon materials at 77 K and their specific surface area. However, porous carbon materials exhibit low hydrogen storage capacity at room temperature due to physical adsorption. While bimetallic nanoalloys demonstrate good hydrogen storage performance at room temperature through chemisorption, the high surface energy of the alloy nanoparticles, leading to agglomeration and reduced cycling stability, hinders their ability to form strong interfacial interactions between the metal and the support.
[0046] The following embodiments of the present invention propose a carbon-based bimetallic hydrogen storage material A rich in surface defects. x B y PANPC-SD (A, B: Pd, Au, Ag, Fe, Co, Ni, Cu) and its preparation method, A x B yPANPC-SD is a composite material of a bimetallic nanoalloy and polyacrylonitrile-derived porous carbon (PANPC) rich in surface defects. PANPC-SD possesses abundant surface defects, providing more anchoring sites for the alloy nanoparticles, thus preventing agglomeration and enhancing the interfacial interaction between the alloy nanoparticles and PANPC-SD. To prepare this composite material, polyacrylonitrile-derived porous carbon is first prepared, then the surface defects of PANPC are manipulated. Subsequently, bimetallic ions are anchored onto the surface of the defect-rich PANPC (PANPC-SD), and A is prepared using an in-situ hydrogen reduction method. x B y / PANPC-SD hydrogen storage material. For example... Figure 15 As shown, it includes the following steps:
[0047] S1: Polyacrylonitrile (PAN) is heat-treated to obtain polyacrylonitrile pre-oxidized carbon; low-temperature heat treatment of PAN in air atmosphere can remove some unstable substances and increase oxygen-containing functional groups in the material. The preparation process is safe and mild, and suitable for large-scale preparation.
[0048] In a specific embodiment, 4-16g of polyacrylonitrile is heated in a muffle furnace at 240-260℃ for 2 hours, with a heating rate of 1-5℃ / min, to obtain PAN pre-oxidized carbon. Preferably, the heating rate is 3℃ / min.
[0049] Furthermore, PAN includes, but is not limited to, fibrous and powder forms, with a molecular weight of 90,000-100,000.
[0050] S2: The polyacrylonitrile pre-oxidized carbon is impregnated in a solution of an activator and calcined under a nitrogen atmosphere to obtain polyacrylonitrile-derived porous carbon (PANPC). Porous carbon materials are typically mixed with the activator using a grinding method, which requires a long time to achieve thorough mixing and is not suitable for large-scale preparation. The solution impregnation method used in this embodiment of the invention allows the carbon precursor to be fully wetted with the activator, is easy to operate, has low risk, and is suitable for large-scale preparation.
[0051] In a specific embodiment, the PAN pre-oxidized carbon prepared in step S1 is impregnated in an aqueous activator solution, with a mass ratio of PAN pre-oxidized carbon to activator of 1:1 to 1:15. The mixture is stirred for 30 min to 24 h, dried at 60-150 °C, and then calcined at 700-900 °C for 90 min in a nitrogen atmosphere. The heating rate is 1-5 °C / min, which affects the pore structure and graphitization of the formed porous carbon. After the atmosphere furnace cools to room temperature, the mixture is washed several times with deionized water and ethanol, and then dried in air at 60 °C to obtain PANPC.
[0052] Preferably, the mass ratio of PAN pre-oxidized carbon to activator is 1:3. Activators include, but are not limited to, KOH, KCl, K2CO3, and mixtures thereof. When the activator contains KOH, the remaining KOH needs to be neutralized with hydrochloric acid aqueous solution before washing in order to remove KOH from the porous carbon.
[0053] S3: The polyacrylonitrile-derived porous carbon is calcined in a protective atmosphere to adjust the vacancies on the polyacrylonitrile-derived porous carbon, thereby obtaining polyacrylonitrile-derived porous carbon (PANPC-SD) rich in surface defects. In existing methods, heteroatom doping and secondary activation are usually used to create more surface defects, which requires more reagents and the secondary activation can also significantly reduce the yield. The method used in this embodiment of the invention is more economical and efficient.
[0054] In a specific embodiment, the protective atmosphere is either air or a H2 / Ar mixed atmosphere. The PANPC prepared in step S2 is calcined in air at 350-450°C for 10-20 min with a heating rate of 1-5°C / min to obtain PANPC-CSD with carbon vacancies. Alternatively, it is calcined in an H2 / Ar mixed atmosphere at 400-850°C for 10-20 min with a heating rate of 1-5°C / min to obtain PANPC-OSD with oxygen vacancies. In this step, it is important to control the heating rate, as it affects the uniformity of surface defects.
[0055] In other applications, the surface defect level of PANPC can be controlled by adjusting other vacancies besides carbon and oxygen vacancies.
[0056] S4: The polyacrylonitrile-derived porous carbon rich in surface defects is dispersed in a solution, and metal source solutions A and B are added dropwise simultaneously. After stirring and drying, the mixture is calcined in a mixed atmosphere of hydrogen and argon to obtain carbon-based bimetallic hydrogen storage material A rich in surface defects. x B y / PANPC-SD; In this embodiment of the invention, a bimetallic source aqueous solution is added dropwise at the same time, which can make the bimetal more fully dispersed on the PANPC surface.
[0057] In a specific embodiment, the product of step S3 is dispersed in 10-50 mL of deionized water and sonicated for 15 min. Simultaneously, aqueous solutions of metal source A and metal source B are added dropwise. Metal A and metal B can be metals such as Pd, Au, Ag, Fe, Co, Cu, etc. Alloy AB is a combination of two different metals A and B. The theoretical content of metal A is 1-10 wt.%, and the theoretical content of metal B is 0-5 wt.%. The mixture is stirred continuously for 3 h, dried at 60-150 °C, and then calcined at 400-900 °C for 120 min in an H2 / Ar mixed atmosphere with a heating rate of 3-5 °C / min (the heating rate will have a certain impact on the interfacial interaction between the metal and PANPC), thereby obtaining metal A. x B y / PANPC-SD (A, B: Pd, Au, Ag, Fe, Co, Ni, Cu).
[0058] Preferably, the rate of addition of aqueous solutions of metal A and metal B should be controlled during the simultaneous addition process, with a slow addition of 1 drop / 10s, so that metal A and metal B are well dispersed on the PANPC surface.
[0059] Preferably, the sources of metal A and metal B can be water-soluble metal salts of the corresponding metals, such as Pd sources including but not limited to palladium nitrate, palladium chloride, and tetrachloropalladium acid.
[0060] By constructing composite materials from PANPC and bimetallic alloy nanoparticles, and through defect manipulation of the porous carbon surface, the anchoring sites of the alloy nanoparticles can be further increased, thereby improving metal utilization and dispersibility. Design A x B y PANPC-SD composite material is used for solid-state hydrogen storage, combining PANPC and A x B y Leveraging the advantages of alloys, a novel solid-state hydrogen storage material has been developed to meet the growing demand. Hydrogen storage performance evaluation tests have shown that this material exhibits high hydrogen storage capacity and good cycle stability, demonstrating broad application prospects in the field of hydrogen storage.
[0061] Example 1
[0062] The preparation and application of a carbon-based bimetallic hydrogen storage material rich in surface defects in this embodiment includes the following steps:
[0063] Step 1: Preparation of PAN pre-oxidized carbon
[0064] 4g of polyacrylonitrile (PAN) was heated in a muffle furnace at 240℃ for 2h at a heating rate of 3℃ / min to obtain PAN pre-oxidized carbon.
[0065] Step 2: Preparation of porous carbon PANPC
[0066] The PAN pre-oxidized carbon prepared in step 1 was impregnated in a KOH aqueous solution at a mass ratio of PAN pre-oxidized carbon to KOH of 1:3. The mixture was stirred for 30 min, dried at 100 °C, and then calcined at 800 °C for 90 min under a nitrogen atmosphere at a heating rate of 3 °C / min. After the atmosphere furnace cooled to room temperature, the KOH was neutralized with hydrochloric acid solution, followed by washing several times with deionized water and ethanol. Finally, it was dried in air at 60 °C to obtain PANPC.
[0067] Step 3: Preparation of PANPC-SD rich in surface defects
[0068] The PANPC prepared in step 2 was calcined at 800℃ for 10 min in a H2 / Ar mixed atmosphere with a heating rate of 5℃ / min to obtain PANPC-OSD with oxygen vacancies.
[0069] Step 4: Preparation of Pd3Ni1 / PANPC-OSD
[0070] The product from step 3 was dispersed in 30 mL of deionized water and sonicated for 15 min, while palladium nitrate aqueous solution and nickel nitrate aqueous solution were added dropwise. The theoretical content of palladium was 3 wt.%, and the theoretical content of nickel was 1 wt.%. The mixture was stirred continuously for 3 h, dried at 90 °C, and then calcined at 400 °C for 120 min in a H2 / Ar mixed atmosphere with a heating rate of 5 °C / min to obtain Pd3Ni1 / PANPC-OSD.
[0071] Example 2
[0072] The preparation and application of a carbon-based bimetallic hydrogen storage material rich in surface defects in this embodiment includes the following steps:
[0073] Step 1: Preparation of PAN pre-oxidized carbon
[0074] 4g of polyacrylonitrile (PAN) was heated in a muffle furnace at 240℃ for 2h at a heating rate of 3℃ / min to obtain PAN pre-oxidized carbon.
[0075] Step 2: Preparation of porous carbon PANPC
[0076] The PAN pre-oxidized carbon prepared in step 1 was impregnated in a KOH aqueous solution at a mass ratio of PAN pre-oxidized carbon to KOH of 1:3. The mixture was stirred for 30 min, dried at 100 °C, and then calcined at 800 °C for 90 min under a nitrogen atmosphere with a heating rate of 3 °C / min. After the furnace cooled to room temperature, the KOH was neutralized with hydrochloric acid solution, followed by washing several times with deionized water and ethanol. Finally, it was dried in air at 60 °C to obtain PANPC.
[0077] Step 3: Preparation of PANPC-SD rich in surface defects
[0078] The PANPC prepared in step 2 was calcined at 400°C for 10 min in air atmosphere with a heating rate of 5°C / min to obtain PANPC-CSD with carbon vacancies.
[0079] Step 4: Preparation of Ag4Ni1 / PANPC-CSD
[0080] The product from step 3 was dispersed in 30 mL of deionized water and sonicated for 15 min, while silver nitrate aqueous solution and nickel nitrate aqueous solution were added dropwise. The theoretical content of metallic silver was 4 wt.%, and the theoretical content of metallic nickel was 1 wt.%. The mixture was stirred continuously for 3 h, dried at 120 °C, and then calcined at 600 °C for 120 min in a H2 / Ar mixed atmosphere with a heating rate of 5 °C / min to obtain Ag4Ni1 / PANPC-CSD.
[0081] Comparative Example 1
[0082] This comparative example provides a method for preparing Pd3 / PANPC-OSD, including the following steps:
[0083] Step 1: Preparation of PAN pre-oxidized carbon
[0084] 4g of polyacrylonitrile (PAN) was heated in a muffle furnace at 240℃ for 2h at a heating rate of 3℃ / min to obtain PAN pre-oxidized carbon.
[0085] Step 2: Preparation of porous carbon PANPC
[0086] The PAN pre-oxidized carbon prepared in step 1 was impregnated in a KOH aqueous solution at a mass ratio of PAN pre-oxidized carbon to KOH of 1:3. The mixture was stirred for 30 min, dried at 100 °C, and then calcined at 800 °C for 90 min under a nitrogen atmosphere with a heating rate of 3 °C / min. After the furnace cooled to room temperature, the KOH was neutralized with hydrochloric acid solution, followed by washing several times with deionized water and ethanol. Finally, it was dried in air at 60 °C to obtain PANPC.
[0087] Step 3: Preparation of PANPC-SD rich in surface defects
[0088] The PANPC prepared in step 2 was calcined at 800℃ for 10 min in a H2 / Ar mixed atmosphere with a heating rate of 5℃ / min to obtain PANPC-OSD with oxygen vacancies.
[0089] Step 4: Preparation of Pd3 / PANPC-CSD
[0090] The product from step 3 was dispersed in 30 mL of deionized water and sonicated for 15 min. Palladium nitrate aqueous solution was then added dropwise. The theoretical content of palladium was 3 wt.%. The mixture was stirred continuously for 3 h, dried at 90 °C, and then calcined at 400 °C for 120 min in a H2 / Ar mixed atmosphere with a heating rate of 5 °C / min to obtain Pd3 / PANPC-CSD.
[0091] Comparative Example 2
[0092] This comparative example provides a method for preparing Ni1 / PANPC-OSD, including the following steps:
[0093] Step 1: Preparation of PAN pre-oxidized carbon
[0094] 4g of polyacrylonitrile (PAN) was heated in a muffle furnace at 240℃ for 2h at a heating rate of 3℃ / min to obtain PAN pre-oxidized carbon.
[0095] Step 2: Preparation of porous carbon PANPC
[0096] The PAN pre-oxidized carbon prepared in step 1 was impregnated in a KOH aqueous solution at a mass ratio of PAN pre-oxidized carbon to KOH of 1:3. The mixture was stirred for 30 min, dried at 100 °C, and then calcined at 800 °C for 90 min under a nitrogen atmosphere with a heating rate of 3 °C / min. After the furnace cooled to room temperature, the KOH was neutralized with hydrochloric acid solution, followed by washing several times with deionized water and ethanol. Finally, it was dried in air at 60 °C to obtain PANPC.
[0097] Step 3: Preparation of PANPC-SD rich in surface defects
[0098] The PANPC prepared in step 2 was calcined at 800℃ for 10 min in a H2 / Ar mixed atmosphere with a heating rate of 5℃ / min to obtain PANPC-OSD with oxygen vacancies.
[0099] Step 4: Preparation of Ni1 / PANPC-OSD
[0100] The product from step 3 was dispersed in 30 mL of deionized water and sonicated for 15 min. A nickel nitrate aqueous solution was added dropwise, with a theoretical nickel content of 1 wt.%. The mixture was stirred continuously for 3 h, dried at 90 °C, and then calcined at 400 °C for 120 min in a H2 / Ar mixed atmosphere with a heating rate of 5 °C / min to obtain Ni1 / PANPC-OSD.
[0101] Comparative Example 3
[0102] This comparative example provides a method for preparing Ag4Ni1 / PANPC, including the following steps:
[0103] Step 1: Preparation of PAN pre-oxidized carbon
[0104] 4g of polyacrylonitrile (PAN) was heated in a muffle furnace at 240℃ for 2h at a heating rate of 3℃ / min to obtain PAN pre-oxidized carbon.
[0105] Step 2: Preparation of porous carbon PANPC
[0106] The PAN pre-oxidized carbon prepared in step 1 was impregnated in a KOH aqueous solution at a mass ratio of PAN pre-oxidized carbon to KOH of 1:3. The mixture was stirred for 30 min, dried at 100 °C, and then calcined at 800 °C for 90 min under a nitrogen atmosphere with a heating rate of 3 °C / min. After the furnace cooled to room temperature, the KOH was neutralized with hydrochloric acid solution, followed by washing several times with deionized water and ethanol. Finally, it was dried in air at 60 °C to obtain PANPC.
[0107] Step 3: Preparation of Ag4Ni1 / PANPC
[0108] The product from step 2 was dispersed in 30 mL of deionized water and sonicated for 15 min, while silver nitrate aqueous solution and nickel nitrate aqueous solution were added dropwise. The theoretical content of metallic silver was 4 wt.%, and the theoretical content of metallic nickel was 1 wt.%. The mixture was stirred continuously for 3 h, dried at 120 °C, and then calcined at 600 °C for 120 min in a H2 / Ar mixed atmosphere with a heating rate of 5 °C / min to obtain Ag4Ni1 / PANPC-CSD.
[0109] The hydrogen storage materials prepared in Example 1, Comparative Example 1, and Comparative Example 2 were subjected to hydrogen storage performance evaluation tests.
[0110] Experimental steps:
[0111] (1) The hydrogen storage performance of Example 1, Comparative Example 1 and Comparative Example 2 was tested using a Seet-type hydrogen storage device. The experimental method was in accordance with GB / T 33291-2016 (Hydride reversible absorption and desorption pressure-composition-isotherm (PCT) test method).
[0112] (2) Test the pressure-composition-isotherm (PCT curve) of the material at temperatures of 77K and 298K;
[0113] (3) The hydrogen storage capacity of the material was tested over time at 77K and 298K.
[0114] (4) Test the cyclic stability of the material at 77K.
[0115] Depend on Figure 9A It can be seen that under the conditions of 77K and 20bar, the hydrogen storage capacity of Pd3Ni1 / PANPC-OSD can reach 7.4 wt.%. Figure 9B It can be seen that the hydrogen storage capacity of Pd3Ni1 / PANPC-OSD is 0.8 wt.% under the conditions of 298 K and 20 bar. The hydrogen storage capacity of Pd3Ni1 / PANPC-OSD is higher than that of Pd3 / PANPC-OSD and Ni1 / PANPC-OSD under the conditions of 77 K and 298 K.
[0116] Depend on Figure 10A and Figure 10B It can be seen that the hydrogen absorption rate of Pd3Ni1 / PANPC-OSD is higher than that of Pd3 / PANPC-OSD and Ni1 / PANPC-OSD under both 77K and 298K conditions.
[0117] Depend on Figure 11 It can be seen that Pd3Ni1 / PANPC-OSD exhibits good cycling stability at 77K.
[0118] The hydrogen storage materials prepared in Example 2 and Comparative Example 3 were subjected to hydrogen storage performance evaluation tests.
[0119] Experimental steps:
[0120] (1) The hydrogen storage performance of Example 2 and Comparative Example 3 was tested using a Seet-type hydrogen storage device. The experimental method was in accordance with GB / T 33291-2016 (Hydride reversible absorption and desorption pressure-composition-isotherm (PCT) test method).
[0121] (2) Test the pressure-composition-isotherm (PCT curve) of the material at temperatures of 77K and 298K.
[0122] (3) The hydrogen storage capacity of the material was tested over time at 77K and 298K.
[0123] (4) Test the cyclic stability of the material at 77K.
[0124] Depend on Figure 12A and Figure 12B It can be seen that the hydrogen storage capacity of Ag4Ni1 / PANPC-CSD is higher than that of Ag4Ni1 / PANPC under both 77K and 298K conditions.
[0125] Depend on Figure 13A It can be seen that the hydrogen absorption rate of Ag4Ni1 / PANPC-CSD at 77K is slightly higher than that of Ag4Ni1 / PANPC, due to... Figure 13B It can be seen that the hydrogen absorption rate at 298K is significantly higher than that of Ag4Ni1 / PANPC.
[0126] Depend on Figure 14 It can be seen that Ag4Ni1 / PANPC-CSD exhibits good cycling stability at 77K.
[0127] This invention presents a carbon-based bimetallic hydrogen storage material rich in surface defects. During preparation, metal ions are initially anchored to the defect-rich PANPC surface through electrostatic interactions, then serve as in-situ growth sites for bimetallic alloy nanoparticles. The bimetallic nanoalloy is uniformly dispersed on the PANPC-SD surface, improving bimetallic utilization and providing more adsorption active sites for hydrogen.
[0128] The carbon-based bimetallic hydrogen storage material rich in surface defects proposed in this invention exhibits excellent hydrogen storage performance, which is attributed to the large specific surface area of PANPC, the abundant surface defects of PANPC-SD, and the synergistic effect between the bimetallic alloy nanoparticles and PANPC-SD. The successful preparation of the composite material solves the key scientific problems of alloy nanoparticle agglomeration and low room temperature hydrogen storage capacity of porous carbon materials.
[0129] In summary, the A proposed in the embodiments of the present invention x B y PANPC-SD (A, B: Pd, Au, Ag, Fe, Co, Ni, Cu) solid-state hydrogen storage material can be used in hydrogen storage. Furthermore, the A component proposed in this embodiment of the invention... x B y The PANPC-SD (A, B: Pd, Au, Ag, Fe, Co, Ni, Cu) composite material is prepared by a simple impregnation method and an in-situ reduction deposition method, which are simple and efficient. The material has high hydrogen storage capacity, rapid hydrogen absorption, low hydrogen desorption temperature and good cycle stability, making it suitable for equipment that requires rapid hydrogen charging and discharging.
[0130] The above description, in conjunction with specific preferred embodiments, provides a further detailed explanation of the present invention. It should not be construed that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art, several equivalent substitutions or obvious modifications can be made without departing from the concept of the present invention, and all such modifications, achieving the same performance or purpose, should be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a carbon-based bimetallic hydrogen storage material rich in surface defects, characterized in that, Includes the following steps: S1: Polyacrylonitrile is subjected to heat treatment in air atmosphere at a temperature of 240-260°C. o C, with a time of 2 hours, yields polyacrylonitrile pre-oxidized carbon; S2: The polyacrylonitrile pre-oxidized carbon is impregnated in a solution of an activator and calcined in a nitrogen atmosphere to obtain polyacrylonitrile-derived porous carbon; the mass ratio of the polyacrylonitrile pre-oxidized carbon to the activator is 1:1 to 1:15, and the activator includes at least one of potassium hydroxide, potassium chloride, and potassium carbonate. S3: The polyacrylonitrile-derived porous carbon is calcined in a protective atmosphere. By adjusting the vacancies on the polyacrylonitrile-derived porous carbon to form carbon vacancies or oxygen vacancies, polyacrylonitrile-derived porous carbon rich in surface defects is obtained, wherein: The protective atmosphere is air, the calcination temperature is 350-450 ℃, the time is 10-20 min, and the heating rate is 1-5. o C / min, to obtain polyacrylonitrile-derived porous carbon with carbon vacancies; or The protective atmosphere is a mixture of hydrogen and argon, the calcination temperature is 400-850 ℃, the time is 10-20 min, and the heating rate is 1-5. o C / min, to obtain polyacrylonitrile-derived porous carbon with oxygen vacancies; S4: The polyacrylonitrile-derived porous carbon rich in surface defects is dispersed in a solution, and metal source solutions A and B are added dropwise. After stirring and drying, it is calcined in a mixed atmosphere of hydrogen and argon, so that metal ions are anchored on the surface of the polyacrylonitrile-derived porous carbon rich in surface defects through electrostatic interaction, serving as in-situ growth sites for bimetallic alloy nanoparticles, thus obtaining a carbon-based bimetallic hydrogen storage material rich in surface defects.
2. The method according to claim 1, characterized in that, In step S1, the molecular weight of the polyacrylonitrile is 90,000 to 100,000.
3. The method according to claim 1, characterized in that, In step S2, the calcination is carried out in a nitrogen atmosphere at a temperature of 700-900 °C for 90 min, with a heating rate of 1-5. o C / min.
4. The method according to claim 1, characterized in that, In step S2, when the polyacrylonitrile pre-oxidized carbon is impregnated in the activator solution, it also includes stirring and drying, calcining in a nitrogen atmosphere, and then cooling, cleaning and drying. The activator contains potassium hydroxide, and the cleaning process further includes using an aqueous hydrochloric acid solution to neutralize any remaining potassium hydroxide, thereby removing potassium hydroxide from the polyacrylonitrile-derived porous carbon.
5. The method according to claim 1, characterized in that, In step S4, metal A is one of palladium, gold, silver, iron, cobalt, nickel, and copper, and metal B is one of palladium, gold, silver, iron, cobalt, nickel, and copper. Metal A is not the same as metal B; The metal A and the metal B are derived from water-soluble metal salts of the corresponding metals, the concentration of metal A is 1-10 wt.%, the concentration of metal B is 0-5 wt.%, and the concentration of metal B is not zero.
6. The method according to claim 1, characterized in that, In step S4, the solution is deionized water and is ultrasonically vibrated for 15 minutes; When the A metal source solution and the B metal source solution are added simultaneously, the dropping rate is 1 drop / 10 s, so that the A metal and the B metal are well dispersed on the surface of the polyacrylonitrile-derived porous carbon rich in surface defects; In step S4, during calcination in a mixed atmosphere of hydrogen and argon, the calcination temperature is 400-900 ℃, the calcination time is 120 min, and the heating rate is 3-5. o C / min.
7. A carbon-based bimetallic hydrogen storage material rich in surface defects, characterized in that, It is obtained using the preparation method of carbon-based bimetallic hydrogen storage material rich in surface defects as described in any one of claims 1 to 6.
Citation Information
Patent Citations
Method for converting waste corn straw into sodium ion battery electrode material
CN107337205A
Nitrogen-oxygen-doped graded porous carbon material, preparation method and application
CN114956040A
Process for preparing carbonaceous hydrogen-storage material with high hydrogen adsorbing amount
CN1401422A
